Handbook of research on development and religion - Clarke, Matthew 1969- (Edward Elgar, 2013)
With 80% of the world's population profesing religious faith, religious belief is a common human characteristic. The sacred texts of each of the world's major religions exhort believers to live a righteous life, including responding to poverty and assisting those with less. This handbook highlights the value of incorporating religion into development studies literature and research.